Pengembangan Bahan Ajar Matematika Terhadap Penalaran Matematis Pada Materi Teorema Phytagoras - Khania Raveliya Putri Anasis; Fitri Alyani (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2021)
The research to develop mathematics teaching materials in digital form that are used to measure the level of reasoning of students on the Pythagorean theorem material. The research method used is development research (R and D) with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The subjects in this research were students of grade VIII Junior High School which consisted of 24 students who were selected by purposive sampling. The results of the study were mathematics teaching materials in digital form to measure mathematical reasoning. Measure the level of mathematical reasoning of the Pythagorean theorem material. A feasibility test of mathematics teaching materials was carried out by material experts with a percentage of 90.63% and a very good category, while from media experts, the percentage was 82.50%  and a good category, mathematics teaching materials were declared eligible to be used as teaching materials for students' independent study. Trial of mathematics teaching materials to measure the level of mathematical reasoning of students who use mathematics teaching materials so that the results obtained are 4 students have low mathematical reasoning, 12 students have moderate mathematical reasoning, and as many as 8 students have high mathematical reasoning.